LCMS MOODLE SEBAGAI MEDIA PEMBELAJARAN BERBASIS KONTEN PADA MATA KULIAH EKONOMETRIKA - Ratna Husein; Yurina Yurina; Sari Yulis Terfiadi (Majelis Pendidikan Aceh, 2022)
The global covid 19 epidemic necessitates universities as higher education institutions continuing to conduct out lecture activities using online means; the learning process carried out by all educational institutions worldwide is to give e-learning-based interactive learning. It is hoped that by utilizing E-learning-based learning materials, learning activities may be carried out in accordance with the output required by each educator. Moodle is a networked learning system that is object-oriented and flexible, and it is one of the solutions available at the Malikussaleh University. This application was created to support instructors in all elements of the learning process by connecting to the internet network via a website page and stressing the social constructionist pedagogy technique. The approach utilized in this study is descriptive qualitative sampling using a saturated sample, which means the sample size is the same as the population size. Data collecting methodology based on observations, interviews, and documents. The interaction between lecturers and students in the learning process is the research's finding. Furthermore, e-learning serves as a discussion platform for lecturers and students, as well as an online exam, making all activities in the learning process highly beneficial.